2019
DOI: 10.1093/imrn/rnz092
|View full text |Cite
|
Sign up to set email alerts
|

G-Tutte Polynomials and Abelian Lie Group Arrangements

Abstract: We introduce and study the notion of the G-Tutte polynomial for a list A of elements in a finitely generated abelian group Γ and an abelian group G, which is defined by counting the number of homomorphisms from associated finite abelian groups to G.The G-Tutte polynomial is a common generalization of the (arithmetic) Tutte polynomial for realizable (arithmetic) matroids, the characteristic quasi-polynomial for integral arrangements, Brändén-Moci's arithmetic version of the partition function of an abelian grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…. It is known that (e.g., [Ath96], [KTT08]) the 1-constituent f 1 A (t) coincides with χ A(R) (t) the characteristic polynomial (e.g., [OT92, Definition 2.52]) of the real hyperplane arrangement (or R-plexification in the sense of [LTY17]…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…. It is known that (e.g., [Ath96], [KTT08]) the 1-constituent f 1 A (t) coincides with χ A(R) (t) the characteristic polynomial (e.g., [OT92, Definition 2.52]) of the real hyperplane arrangement (or R-plexification in the sense of [LTY17]…”
Section: Preliminariesmentioning
confidence: 99%
“…Later on, Kamiya-Takemura-Terao showed that #M(A; Z ℓ , Z/qZ) is actually a quasi-polynomial in q [KTT08], and left the task of understanding the constituents of this quasi-polynomial to be an interesting problem. A number of attempts have been made in order to tackle the problem (e.g., [KTT08], [LTY17], [DFM17]), especially, two interpretations for every constituent via subspace and toric viewpoints have been found [TY18]. The mentioning establishments open a new direction for studying the combinatorics and topology of hyperplane and toric arrangements in one single quasi-polynomial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture them requires a richer combinatorial object, such as the matroids over Z of [27]. The requisite data also appear in the G-Tutte polynomial of [45], and Theorem 5.5 of that work explains how to recover from the G-Tutte polynomial every constituent of the characteristic quasi-polynomial, which is up to a sign the evaluation Q(1 − t, 0) of the Tutte quasi-polynomial. = m 1 (A) m 2 (A).…”
Section: Arithmetic Matroidsmentioning
confidence: 99%
“…This quasi-polynomial was defined to evaluate the cardinality of the complement of the q-reduced arrangement A(Z q ) in Z q . Then the characteristic polynomials of the hyperplane and toric arrangements coincide with the first and the last constituents of the characteristic quasi-polynomial, respectively ( [KTT08], [LTY17]).…”
Section: Introductionmentioning
confidence: 99%